Attitude Stabilization of a Magnetic Torquer and Gravity Gradient-based CubeSat Using ANFIS - Bekuretsion, Tsegaye (ASTU, 2024)
Tiny box-shaped satellites called CubeSat’s are typically sent into low Earth orbit to survey the planet, try out cutting-edge communications systems, or run miniature experiments. This study's objective is to develop and improve an effective Attitude Control System (ACS) for the CubeSat. Magnetic coils are introduced to improve the three axis stabilization and the pointing capabilities of a gravity gradient stabilized satellite because these attributes are limited. A steady current switched in two directions, is applied to the magnetic coils that surrounding the satellite's X, Y, and Z axes. This produces a magnetic dipole moment that interacts with the geomagnetic field, generating a torque used to control the rotation of the CubeSat. A problem is that as the geomagnetic field changes in both strength and direction, magnetic control becomes non-linear and time-dependent. The ANFIS controller was used as the approach for controlling magnetic coils. Full State Feedback Controller provides the training data for Adaptive Neuro-Fuzzy Inference System(ANFIS). The Ackermann Formula is employed to calculate the state feedback gain matrix (K), which requires pre-defined poles. The Bessel polynomial method is utilized to provide these pre defined poles. By simulating a mathematical model of a CubeSat with consideration for gravity gradient stabilization and magnetorquer using MATLAB, the performance of the controller was evaluated. Though both ANFIS and FSF controllers provided good results in the analysis, ANFIS controlled Cubesats had slightly higher peak values for roll (10o ), pitch (30o ), and yaw (20.5291o ), which indicated an enhancement of the satellite’s ability to rapidly adjust itself. On the other hand, Full State Feedback (FSF) was highly effective at stabilizing and keeping the satellite on course with minimum error rate. The choice between the two depends on mission requirements and computational considerations.
Keywords: Attitude control system, Full State Feedback Controller, ANFIS, Magenetorquer, Ackermann, Bessel polynomial